The DIS arbitration rules an article-by-article commentary - Flecke-Giammarco, Gustav; Boog, Christopher; Elsing, Siegfried H.; Heckel, Peter, 1952-; Meier, Anke, 1973- (Kluwer Law International B.V., 2020)
The DIS Arbitration Rules' is the first practical commentary on the 2018 DIS Arbitration Rules. The new rules of the German Arbitration Institute (DIS) entered into force on 1 March 2018. Drafted over an intense period of eighteen months by a committee of globally recognized experts with the active participation of nearly three hundred arbitration practitioners, the DIS Rules stand poised to attract parties seeking dispute resolution not only in Germany but also internationally. This book, written by the drafters themselves, with a comprehensive article-by-article commentary, is filled with practical insights and recommendations regarding the application of the Rules. The book introduces important novelties and highlights changes to the 1998 Arbitration Rules, and it provides in-depth information on the purpose of each provision.